Kecakapan Soft Skill dan Hard Skill bagi Akuntan Profesional dan Andal - Fitria Auldri Desiana; Nurul Fauziyyah (MIZANIA: Jurnal Ekonomi Dan Akuntansi, 2023)
In the 4.0 era, individuals must present new skills in all activities carried out. Forms of skills that are needed at this time are soft skills and hard skills. This study was conducted with the aim of providing an overview and persuasion that an accountant must create a character in his field through mastery of competence and mastery of supporting soft skills and hard skills in order to be able to carry out his profession professionally and reliably. The capability of accountants regarding soft skills and hard skills must be developed in order to help wisely respond to problems that arise suddenly in the world of work and provide a comprehensive solution to these problems armed with the competencies and skills of the soft skills and hard skills they have. To overcome it, an analysis needs to be carried out to find out what and how important a person's capabilities are in the world of work. This study uses literature review methods. The results found that accounting students or an accountant need to have soft skills and hard skills including future skills so they are not eliminated in the world of work and can compete with other workers.